Preterm Birth Prevention Post-Conization: A Model of Cervical Length Screening with Targeted Cerclage - Kindinger,LM; Kyrgiou,M; MacIntyre,DA; Cacciatore,S; Yulia,A; Cook,J; Terzidou,V; Teoh,TG; Bennett,P (PLOS One, 2016)
Women with a history of excisional treatment (conization) for cervical intra-epithelial neoplasia (CIN) are at increased risk of preterm birth, perinatal morbidity and mortality in subsequent pregnancy. We aimed to develop a screening model to effectively differentiate pregnancies post-conization into low- and high-risk for preterm birth, and to evaluate the impact of suture material on the efficacy of ultrasound indicated cervical cerclage. We analysed longitudinal cervical length (CL) data from 725 pregnant women post-conization attending preterm surveillance clinics at three London university Hospitals over a ten year period (2004–2014). Rates of preterm birth <37 weeks after targeted cerclage for CL<25mm were compared with local and national background rates and expected rates for this cohort. Rates for cerclage using monofilament or braided suture material were also compared. Of 725 women post-conization 13.5% (98/725) received an ultrasound indicated cerclage and 9.7% (70/725) delivered prematurely, <37weeks; 24.5% (24/98) of these despite insertion of cerclage. The preterm birth rate was lower for those that had monofilament (9/60, 15%) versus braided (15/38, 40%) cerclage (RR 0.7, 95% CI 0.54 to 0.94, P = 0.008). Accuracy parameters of interval reduction in CL between longitudinal second trimester screenings were calculated to identify women at low risk of preterm birth, who could safely discontinue surveillance. A reduction of CL <10% between screening timepoints predicts term birth, >37weeks. Our triage model enables timely discharge of low risk women, eliminating 36% of unnecessary follow-up CL scans. We demonstrate that preterm birth in women post-conization may be reduced by targeted cervical cerclage. Cerclage efficacy is however suture material-dependant: monofilament is preferable to braided suture. The introduction of triage prediction models has the potential to reduce the number of unnecessary CL scan for women at low risk of